Toward a Gender-Sensitive Approach of Psychiatric Rehabilitation in Autism Spectrum Disorder (ASD): A Systematic Review of Women Needs in the Domains of Romantic Relationships and Reproductive Health - Dubreucq, Marine; Dubreucq, Julien (Frontiers in Psychiatry, 2021)
Later age of diagnosis, better expressive behaviors, increased use of camouflage strategies but also increased psychiatric symptoms, more unmet needs and a general lower quality of life are characteristics often associated with female sex in Autism Spectrum Disorder (ASD). Psychiatric rehabilitation (i.e. psychoeducation, social skills training, cognitive behavior therapy, cognitive remediation and supported employment) has shown small to moderate effectiveness in improving patient’s outcomes in ASD. Few sex-differences have been found in the response to psychiatric rehabilitation. This might be related to the predominance of males in research samples but also to the lack of programs directly addressing women’s unmet needs. The present paper aims at describing the interventions designed for women with ASD in Grenoble’s FondaMental Advanced Center of Expertise for ASD and Reference Center for Psychiatric Rehabilitation. Two domains where women report unmet needs were considered: i) romantic relationships and prevention of sexual abuse; ii) reproductive health and parenting. We conducted a rapid review on ASD women’s needs for psychiatric rehabilitation in these two domains and described the individual and group interventions designed for women with ASD (intervention of a trained midwife, group-based interventions on reproductive health and sexuality). We included two anonymized case vignettes illustrating recovery-oriented interventions for women with ASD (romantic relationships; preconception to post-partum care). We discussed the potential implications for improving women’s access to psychiatric and psychosocial treatment, for designing gender-sensitive recovery-oriented interventions (e.g. group-based intervention on sexuality in autistic women; case-management from preconception to post-partum care) and for future research.